Blood to Bloodless: Sclerotherapy in the Management of Mucocele - Kime Yama; Cheena Singh; P. Shivasakthi; Ambika Gupta (Journal of Indian Academy of Oral Medicine and Radiology)
Background: Mucocele can appear at various locations in the body, including the oral cavity. The lower lip is frequently affected. Although surgery is the most commonly used treatment modality, some patients may not be willing to undergo the surgery. In these cases, nonsurgical treatment options should be explored. Objective: This study evaluates the effect of sclerotherapy (3% sodium tetradecyl sulfate) in oral mucoceles. Methods: Nonsurgical treatment of oral mucocele by intralesional injection of sodium tetradecyl sulfate was performed on 10 patients who were not willing for surgical treatment of mucocele. Results: All 10 patients showed regression of the lesion after 1–6 consecutive injections at weekly intervals. No recurrences were observed on three-month follow-up. Conclusion: Sclerotherapy, being a noninvasive, simpler, and bloodless procedure, helps reduce the complications associated with surgery of the oral mucoceles and can be considered as an alternate treatment modality.